Epidemiology and Risk Factors Associated with Surgical Site Infection Following Thoracic Aortic Surgery. (4th October 2017) - Morikane, Keita
Abstract: Background: Surgical site infection (SSI) is one of the most common healthcare-associated infections (HAIs). SSI following surgery on thoracic aorta, such as mediastinis and infection of reconstructed vessel, is often critical, but its epidemiology has not been well described. This study aims to describe the epidemiology and assess risk factors associated with SSI following thoracic aortic surgery (TAS) in Japan, using a Japanese national database for HAIs. Methods: Data on TAS performed between 2012 and 2014 were extracted from a national surveillance system for healthcare-associated infections, Japan Nosocomial Infections Surveillance (JANIS). Risk factors associated with SSI following TAS were assessed using multivariate logistic regression analysis. Results: The overall incidence of SSI following TAS was 4.1% (146/3, 538). The proportion of incisional SSI and organ/space SSI was similar (71 and 75, respectively). Staphylococci were the major causative pathogens. Among the three traditional risk factors included in the National Nosocomial Infections Surveillance (NNIS) risk index, American Society of Anesthesiologists (ASA) score and wound class were insignificant in predicting SSI, leaving duration of operation the sole significant risk factor. Additional risk factors were identified, including emergency and male gender. Conclusion: Incidence of SSI following TAS was substantial. Risk factors associated with SSI following TAS were identified. In order to accurately compare hospital performance regarding SSI following TAS, emergency and gender should be incorporated into risk adjustment model. Disclosures: All authors: No reported disclosures.